1999
DOI: 10.1021/jf9900985
|View full text |Cite
|
Sign up to set email alerts
|

Paprika (Capsicum annuum) Oleoresin Extraction with Supercritical Carbon Dioxide

Abstract: Paprika oleoresin was fractionated by extraction with supercritical carbon dioxide (SCF-CO(2)). Higher extraction volumes, increasing extraction pressures, and similarly, the use of cosolvents such as 1% ethanol or acetone resulted in higher pigment yields. Within the 2000-7000 psi range, total oleoresin yield always approached 100%. Pigments isolated at lower pressures consisted almost exclusively of beta-carotene, while pigments obtained at higher pressures contained a greater proportion of red carotenoids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 12 publications
3
29
1
4
Order By: Relevance
“…SFE methods particularly using SC-CO 2 for the carotenoid extraction from fruits and vegetables including capsicum have been described by many authors (Illés et al 1999;Uquiche et al 2004;Arimboor et al 2006). In SC-CO 2 extraction, larger extraction volume, higher pressure, lower particle size and the use of ethanol or acetone as co-solvents have been reported to yield more pigments from red pepper (Jaren-Galan et al 1999;Ambrogi et al 2002;Uquiche et al 2004;Tepic et al 2009). It has also been shown that the proportion of red carotenoids such as capsorubin, capsanthin and zeaxanthin increased with the increase in extraction pressure (Jaren-Galan et al 1999).…”
Section: Extraction and Pretreatment Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…SFE methods particularly using SC-CO 2 for the carotenoid extraction from fruits and vegetables including capsicum have been described by many authors (Illés et al 1999;Uquiche et al 2004;Arimboor et al 2006). In SC-CO 2 extraction, larger extraction volume, higher pressure, lower particle size and the use of ethanol or acetone as co-solvents have been reported to yield more pigments from red pepper (Jaren-Galan et al 1999;Ambrogi et al 2002;Uquiche et al 2004;Tepic et al 2009). It has also been shown that the proportion of red carotenoids such as capsorubin, capsanthin and zeaxanthin increased with the increase in extraction pressure (Jaren-Galan et al 1999).…”
Section: Extraction and Pretreatment Of Samplesmentioning
confidence: 99%
“…In SC-CO 2 extraction, larger extraction volume, higher pressure, lower particle size and the use of ethanol or acetone as co-solvents have been reported to yield more pigments from red pepper (Jaren-Galan et al 1999;Ambrogi et al 2002;Uquiche et al 2004;Tepic et al 2009). It has also been shown that the proportion of red carotenoids such as capsorubin, capsanthin and zeaxanthin increased with the increase in extraction pressure (Jaren-Galan et al 1999). On line monitoring of SC-CO 2 extraction of paprika carotenoids using near infrared-visible detector showed that the ratio of β-carotene+ free xanthophylls to total carotenoids in the recovered oleoresin diminished from nearly 50 % at the beginning down to 10 % at the end of extraction (Ambrogi et al 2002).…”
Section: Extraction and Pretreatment Of Samplesmentioning
confidence: 99%
“…Jalapeño peletizado 4-4,5 h a 32 ó 3-4 L min La P y la T afectan a la solubilidad de la ORP en CO 2 , aunque ello también depende de la materia prima En general, la temperatura de 40 °C presenta una mayor selectividad en la extracción con CO 2 (Jarén-Galán et al, 1999). Aunque la mayoría de los autores recomiendan 40 °C en vez de 55 °C (Tablas 1 y 2), Daood et al (2002) obtuvieron un máximo de rendimiento de extracción (~11,5%) a 40 MPa y 55 °C.…”
Section: Elección De Condicionesunclassified
“…Jarén-Galán et al (1999) triplicaron la extracción de carotenoides presentes en la ORP aumentando la presión de 13,9 a 41,34 MPa, mientras que Daood et al (2005) incluso quintuplicaron esta proporción entre 10 y 40 MPa. Daood et al (2002) demostraron para ORP picante que para una misma temperatura y comparando presiones de 20, 30 y 40 MPa, a las P más altas se reducía la razón disolvente CO 2 /materia prima (p/p) necesario para obtener un determinado rendimiento.…”
Section: Elección De Condicionesunclassified
See 1 more Smart Citation